All-Solid-State Supercapacitor with High Volumetric Energy for Flexible Application. Issue 13 (20th August 2019) - Shen, Yu Kang; Lv, You Yin; Chi, Hong Zhong; Xi, Junhua; Xiong, Qinqin; Qin, Haiying
Abstract : Deformability and compact energy density are urgently needed for power supplies to cater to today's increasingly multifunctional consumer electronics. Here, a flexible and self-supporting composite electrode, in which manganese oxide directly grows on surfaces of the reduced graphene oxide and the interconnected porous framework of the hydrogel is retained, was fabricated by electrochemical deposition of manganese dioxide in graphene hydrogel. Thanks to the contribution of pseudocapacitance and the unchanged volume of the hydrogel, the introduction of manganese oxide helps to lift the volumetric capacitance of the electrode by more than 400%, from 103.6 to 417.8 F cm −3 . The solid-state asymmetric supercapacitor, composed of an activated carbon electrode and an as-prepared composite electrode, has a capacitance of 67.7 F cm −3 . The series connected supercapacitor not only successfully illuminates a white light-emitting diode bulb, but also works steadily under deformation conditions.